Identification of Goosegrass (Eleusine indica) Biotypes Resistant to Preemergence-Applied Oxadiazon. (24th August 2017) - McElroy, J. Scott; Head, William B.; Wehtje, Glenn R.; Spak, David
Abstract : Goosegrass biotypes from golf courses in Richmond, VA (CCV) and New Bern, NC (RB) historically treated with oxadiazon were identified as resistant compared to susceptible standard (PBU) based on comparisons of oxadiazon applied preemergence at increasing rates (0.03 to 2.24 kg ha -1 ). Oxadiazon at rates ≤ 2.24 kg ha -1 rate did not prevent emergence of suspected resistant CCV and RB seedlings. PBU emergence was completely prevented at 0.14 kg ha -1 . Based on percent seedling emergence relative to non-treated and percent above-ground biomass reduction relative to non-treated, the oxadiazon rate at which emergence would be reduced 50% (I50 ) or 90% (I90 ) ranged from 0.12 to 0.18 kg ha -1 or 10.83 to 85.57 kg ha -1, respectively for suspected resistant CCV and RB, compared to 0.03 to 0.4 kg ha -1 or 0.12 to 0.19 kg ha -1, respectively for susceptible standard PBU. Seedling emergence data predicted 7.9 and 3.0 times greater I90 values for CCV and RB, respectively compared to biomass data. All three biotypes were completely controlled by preemergence applied labeled rates of prodiamine and indaziflam. This is the first peer-reviewed report of evolved weed resistance to oxadiazon.